Preliminary analysis of habitat utilization by woodland caribou in northwestern Ontario using satellite telemetry - Hillis, T.L.; Mallory, F.F.; Dalton, W.J.; Smiegielski, J. (Rangifer, 1998)
Locational data collected over a one year period from 10 female woodland caribou, Rangifer tarandus caribou, collared with Argos satellite collars in northwestern Ontario, Canada were superimposed on supervised Landsat images using Geographical Information System (GIS) technology. Landscape parameters, land cover classifications, and drainage were utilized to create the basemap. Using ARCVIEW software, all digital fixes from collared caribou with information of date, time, and activity status were overlain on the basemap to facilitate a preliminary analysis of habitat use in this species. Results supported the conclusions (1) that woodland caribou in northwestern Ontario select habitats containing high to moderate conifer cover and avoided disturbed areas and shrub-rich habitats, (2) that seasonal changes in habitat utilization occurs in females of this species, and (3) that satellite telemetry technology can be employed in the boreal forest ecosystem to assess habitat utilization by large ungulate species.